FAKTOR FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK (Studi Kasus Pada Wajib Pajak Orang Pribadi di KPP Pratama Semarang Candisari) - Sentika Adiguna, 13.05.62.0031; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
This study aims to tes pen fiscal service order, tax awareness, tax knowlwdge, taxpayer financial condition and tax sanction on personal taxpayer compliance level in KPP Pratama Candisari Semarang. This research is a quantitative research that is analyzed using SPSS 16 program. The population in this research is all taxpayers registered in KPP Pratama Candisari Semarang with criteria of taxpayer of private person who own business / free work. Samples were taken with system probability sampling and obtained 125 respondents .. The data is then analyzed by using multiple linear regression test.. The result of this research is taxpayer service, taxpayer awareness and tax sanction have an effect on taxpayer compliance level of person in KPP Pratama Candisari Semarang, while the variable of tax knowledge and financial condition of taxpayer does not have influence to taxpayer compliance level of person in KPP Pratama Candisari Semarang. Keywords: Tax Compliance, Fiscal Services, Tax Awareness, Knowledge Tax, Financial Condition of Taxpayers and Tax Sanctions.